Felids of Sebangau: Camera trapping to estimate activity patterns and population abundance in Central Kalimantan, Indonesia - ADUL ADUL; BERNAT RIPOLL; SUWIDO H LIMIN; SUSAN M CHEYNE (Biodiversitas Journal of Biological Diversity, 2015)
Adul, Ripoll B, Limin SH, Cheyne SM. 2015. Felids of Sebangau: Camera trapping to estimate activity patterns and population abundance in Central Kalimantan, Indonesia. Biodiversitas 16: 151-155. We present data from a seven year camera trappingproject in the Natural Laboratory of Peat-Swamp Forest in the Sebangau Catchment, Central Kalimantan, Indonesia (2008-2015). Theproject has identified four of the five felids on Borneo: Sunda clouded leopard (Neofelis diardi; macan dahan), flat-headed cat(Prionailurus planiceps; kucing tandang), marbled cat (Pardofelis marmorata; kucing batu) and leopard cat (Prionailurus bengalensis;kucing kuwuk). All of these species are protected by Indonesian Law (PP. 7/1999) and are listed on the IUCN Red List. The four specieshave clearly defined activity budgets, especially the smaller cats, to allow niche partitioning. We have identified this forest block as animportant area for numbers of all four species in the global context of cat populations. The bay cat (Pardofelis badia (kucing merah) has not been found in tropical peat-swamp forest at time of writing.